Private regulation of labor standards in global supply chains : problems, progress, and prospects - Kuruvilla, Sarosh (ILR Press, an imprint of Cornell University Press, 2021)
"This book outlines the major problems in corporate voluntary regulation of labor standards in global supply chains, and shows the progress such regulation has made thus far in improving the lives of workers in the global supply chain. It then presents pathways by which private regulation can be improved"--Provided by publisher.